ROMANIAN REVIEW OF REGIONAL STUDIES, VOL. V, NR. 2, 2009 - COCEAN, Pompei (2009)
Romanian Review of Regional Studies, edited by the Centre for Regional Geography since 2005, is a semiannual scholarly journal which aims at disseminating the results from the research in the field of regional studies and promoting the exchange of ideas and experience between academics, researchers, and practitioners in the field of Regional Geography and other closely-related fields.